2014
DOI: 10.3233/jvr-130662
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive postsecondary education: Reimagining the transition trajectories of vocational rehabilitation clients with intellectual disabilities

Abstract: Persons who participate in postsecondary education (PSE) enjoy improved prospects for securing gainful employment and realizing greater independence. Historically, state vocational rehabilitation (VR) agencies have supported persons with disabilities to participate in PSE as a pathway to future employment. However, until recently PSE was not considered as an option for individuals with intellectual disabilities (ID) who were frequently encouraged to transition directly from school to employment or placements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…People with intellectual disabilities are underrepresented in colleges and universities compared to students with other impairments (Yamamoto, Stodden, and Folk 2014). Also, disability policy and accommodation mainly focus on issues such as assistive technology and access to buildings rather than different barriers (e.g.…”
Section: The International Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…People with intellectual disabilities are underrepresented in colleges and universities compared to students with other impairments (Yamamoto, Stodden, and Folk 2014). Also, disability policy and accommodation mainly focus on issues such as assistive technology and access to buildings rather than different barriers (e.g.…”
Section: The International Contextmentioning
confidence: 99%
“…Research has demonstrated that students with intellectual disabilities who participated in inclusive PSE programmes experience increased satisfaction in domains such as self-esteem, self-respect, interpersonal relationships, self-determination and social inclusion (Hughson, Moodie, and Uditsky 2006;Kleinert et al 2012;Uditsky and Hughson 2012). Also, students with intellectual disabilities who have graduated from PSE are reported to have improved their employment opportunities (Hughson, Moodie, and Uditsky 2006;Kleinert et al 2012;Yamamoto, Stodden, and Folk 2014). It has been reported in Iceland, Europe and America that people with intellectual disabilities are underrepresented in the labour market and on average earn lower wages than the general population (Social Science Research Institute 2013; Walker 2014; Moore and Schelling 2015).…”
Section: The International Contextmentioning
confidence: 99%
“…There is growing evidence that by undertaking such programmes, students with intellectual disabilities improve their self-esteem and confidence [27], interpersonal relationships, self-determination, social inclusion [28], and employment opportunities [29]. Consequently, from this perspective, there are strong economic and moral considerations [30] for including those who have traditionally been excluded in higher education. For Stodden and Mruzek [31], combating such exclusion is essential to ensure that economies can develop while those at most risk can become part of the knowledge society and through the transformative power of their voice, can make their contribution.…”
Section: The Trinity Centre For People With Intellectual Disabilities (Tcpid)mentioning
confidence: 99%
“…postsecondary education college programs designed for individuals with IDD (PSEs) open doors to a broad range of experiences, affiliate learners to a community that fosters personal growth and development, and offer greater access to independence, employment, and economic selfsufficiency (Thoma et al, 2011;Yamamoto, Stodden, & Folk, 2014). However, research on the benefits or risks associated with attending PSEs is generally limited (McEathron, Beuhring, Maynard, & Mavis, 2011).…”
mentioning
confidence: 99%